Mifepristone versus intracervical prostaglandin E2 gel for cervical ripening in primigravid patients at term - Sah, Manoj Kumar; Padhye, Saraswati M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The cervix has to play dual role in human reproduction. During pregnancy, it should remain firm and closed allowing the fetus to grow in utero until functional maturity is attained while during labour it should soften and dilate, allowing the fetus to pass through the birth canal. Objective of present study was to know and compare the effect of oral Mifepristone with intracervical dinoprostone gel for cervical priming prior to induction of labour at term in an unfavorable cervix of primigravida. Methods: This was prospective randomized comparative study. 100 primigravid patients were included, 50 were placed in each group A and B. Tablet Mifepristone 200mg orally was given in group A patients and intracervical dinoprostone gel induction was done in group B patients. Pre induction Bishop’s score was noted at beginning to compare improvement in Bishop’s score after induction. Mode of delivery and induction to delivery interval in both the groups were studied. Results: After induction with Mifepristone 76% women had successful cervical ripening as compared to 56% with dinoprostone. Rate of vaginal delivery was 70% with Mifepristone and 58% with dinoprostone. There was no significant difference in induction to delivery interval between the groups. Ten percent and 2% belonging to mifepristone and dinoprostone group respectively, required NICU admissions. Conclusions: Mifepristone is more effective than dinoprostone for preinduction cervical ripening as it has high success rate of achieving cervical ripening, however there is no significant difference in the vaginal delivery rate and other maternal and fetal outcome.